Improving Mass Efficiency in Ammonia Production from Hydrogen and Nitrogen Through Optimizing Operating Condition - Verlanda, Fransiskus F.; Widyadhana, Azidane A.; Siahaan, David J. G.; Rahman, M. Aulia D. (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
As one of the main raw materials in the fertilizer industry, global ammonia consumption continued to increase from 2010 to 2020, at a rate of about 1.81% per year. The ammonia production process is divided into four main stages: Feed Gas Pre-Treatment, Syngas Generation, Syngas Purification, and Ammonia Synthesis. The raw materials required for the ammonia production process include natural gas, steam, and air. To meet the increasing demand for ammonia, a production process with high efficiency is required in order to produce high conversion. One of the efforts to increase efficiency is through the addition of recycling, compressors, and TEE in the Aspen HYSYS simulation. With this increase in conversion, it is expected that the quantity of ammonia products produced will be greater, and the use of materials and energy will be more optimal. The method used to increase mass efficiency is by adding recycling, compressors, TEE, and adjusting the pressure in the separator. From this simulation, it can be concluded that our simulation shows an increase in mass efficiency compared to the simulation without the addition of compressors, recycle, and TEE in Aspen HYSYS. We can increase the mass conversion from 97% up to 99.09%. Net energy of the process can be reduced from 2.59e+8 to 1.64e+8 BTU/h. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).